Apathy in Older Adults With and Without Dementia: An Integrative Review of Barriers and Facilitators to Care - Aderonke Agboji; Shannon Freeman; Davina Banner; Annie Duchesne; Joshua Armstrong; Melinda Martin-Khan (SAGE Open, 2024)
Despite the detrimental impact of apathy on the cognition, functional abilities, and quality of life of older people, it is often under-rated and under-managed. This integrative review provides a comprehensive overview of the barriers as well as potential facilitators to optimal care for older adults with apathy. A systematic search for relevant literature using Whittemore and Knafl’s framework was conducted to identify factors that inhibit or facilitate optimal detection and intervention for apathy in older people with and without dementia. Four key barriers were identified including lack of standardized definition of apathy, lack of awareness, overlap with other disorders, and methodological limitations of clinical trials. Key facilitators included involvement of the dyad (persons with apathy and their families/formal caregivers), education, training and experience, and adoption of new and innovative method of screening and intervention. To provide optimal care for older people with apathy, there is need to adopt a multifaceted approach, including the development of precise definition of apathy, consideration of person-centered approach, caregiver training, and best practice guidelines for management of apathy. Future research and practice into effective interventions for management of apathy in older adults, and enhanced education and training for healthcare professionals, are needed to ensure quality of care for older adults with apathy.